The importance of port logistics on the cost of transport and stowage of cereals at ports - Cazorla A. (Feed manufacturing in Southern Europe: New challenges, 1997)
The main elements which make up the CIF for cereal transport are described. This cost is due to the inland transport (trucks, train and river boat), port reception and stowage, loading or boarding vessels, maritime fees and assurance. Each element is described following the experience of the Port of Rouen, which is the first exporting port of cereals in the EU. From this port, between 5 and 9 Mt of cereals have been exported to the world market. The influence of each inland transport route from the loading place to the loading vessels (trucks 70 per cent, train 13 per cent and river boats 7 per cent) on the cost of cereal transport is discussed. The main destination of cereals exported by Rouen into the EU was Southern European countries (Portugal, Spain, Italy and Greece), reaching 30 per cent total exports. It can be concluded that in the port of Rouen, the cost of CIF is due to charges of inland and vessel transport, and the 20 per cent cost remaining is due to the port activity.
South European Feed Manufacturers Conference, 1996/05/09-11, Reus (Spain)